Testing the Functionality of Joint Zoonotic Disease Electronic Surveillance and Reporting Systems through a Pandemic Influenza Full-Scale Simulation Exercise in Jordan - Rebecca Badra; Alaa Hamdallah; Nour Abu Elizz; Majid Hawawsheh; Heba Mahrous; Amgad Abdalla Elkholy; Abdinasir Abubakar; Mohammad Alhawarat; Lora Alsawalha; Ghazi Kayali (Zoonotic Diseases, 2024)
Zoonotic disease surveillance and response simulation exercises are an important tool to assess national infrastructures and mechanisms supporting joint zoonotic disease surveillance and information sharing across sectors. In December 2022, the Jordanian Ministries of Health and Agriculture, supported by the World Health Organization Country Office, conducted a 10-day full-scale simulation exercise in Amman, Jordan, to evaluate the linkage between their electronic surveillance and response systems. An exercise management team designed a realistic fictitious scenario of an outbreak of avian influenza on a poultry farm that subsequently led to human infections. The functions and actions tested included all aspects of outbreak management, from initial reporting to conclusion. Debriefings and an after-action review were conducted after the activities were completed. Gaps in both ministries’ surveillance systems, epidemiological investigations, biosafety and biosecurity, sample collection, sample transport, laboratories, interventions, and coordination were identified. This simulation exercise was a unique exercise focusing on multiple technical and operational capacities that related to the joint response to potential zoonotic disease outbreaks and real-time information sharing between the sectors under the One Health approach. This exercise is a step towards the operationalization of the One Health approach in Jordan, building on the coordination mechanisms already in place.